DETERMINANTS OF ADOPTION OF RECOMMENDED IRISH POTATO (Solanum tuberosum) PRODUCTION TECHNOLOGIES BY SMALLHOLDER FARMERS IN PLATEAU STATE, NIGERIA - A. A., Girei,; E. S., Salau,; Audu, S.I.; Darason, Y. M (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2020)
The study assessed the determinants of adoption of recommended Irish Potato production technologies by small scale farmers in northern agricultural zone of Plateau State. A total of 150 farmers were drawn through multistage sampling procedure for the study. Data were analysed using descriptive and inferential statistical tools. The mean age of the respondents was 45 years. Most respondents (55.3%) were female, implying that women invested more into Irish potato production than their male counterpart. A vast majority (98%) of the respondents had some form of education qualification in the study area. The mean years of farming experience was 23 years, with mean household size of 9 persons. Farmers had mean total land size of 3.2 hectares and mean of 1.7 hectares of farm land allocated for Irish potato farming. The mean annual income of farmers was estimated at N895,800. The predictors that significantly determined the adoption of recommended Irish potato production technologies were age, number of extension contacts and level of education. It was recommended that deliberate and consistent intensification and diversification of Nigeria’s public extension is pertinent be engaged in by stakeholders in the private sector and government.